Respon Pertumbuhan dan Hasil Panen Tanaman Sawi (Brassica juncae L.) Terhadap Pemberian POC Limbah Cangkang Telur dan Kulit Melon - Vivin Andriani; Ngadiani; Gusti Azzahra Widiaura (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to analyze the ability of liquid organic fertilizer with the basic ingredients of waste melon and eggshells on the growth and production of mustard plants, and determine the effective concentration of the growth and production of mustard plants. Liquid organic fertilizer is made with the composition of 3kg melon skin waste, 1kg eggshell, 7liter water, 1kg sugar and 1liter EM4. Four treatments were given with the concentration of 0% treatment as control, 10%, 15%, 20% for 30 days after mustard plants were treated. This study used a Completely Randomized Design consisting of 4 treatments with 6 replications. ANOVA test results showed that the four concentrations did not significantly influence height, number of leaves, and significant effect on productivity (wet weight) of mustard greens. LSD / BNT test showed that there was only a significant difference in treatment 3 for treatment 1, 2, and treatment 4 for wet weight. And no significant effect (p> 0.05) with the application of liquid organic fertilizer from melon and eggshell skin waste on the number of leaves and plant height. The conclusion of this research is that the application of liquid organic fertilizer from melon and eggshell skin waste with a concentration of 15% is an effective concentration and significantly influences the fresh weight of mustard plants.